2021
DOI: 10.3389/fmed.2021.639652
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Prospective Registration and Quality of Systematic Reviews in Type 2 Diabetes Mellitus: A Meta-epidemiological Study

Abstract: Background: We sought to investigate the methodological and reporting quality of published systematic reviews describing randomized controlled trials in type 2 diabetes mellitus and analyze their association with status of protocol registration.Methods: We searched the PubMed database and identified non-Cochrane systematic reviews, with or without meta-analysis, reporting on type 2 diabetes mellitus and published between 2005 and 2018. We then randomly selected 20% of these reviews in each year, and performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Despite the availability of reporting guidelines, the poor confidence ratings in this study suggest that SR authors do not adequately adhere to such guidelines. Our results also confirm the finding that SRs with review protocols have more strengths than SRs without review protocols [ 19 , 20 , 21 , 22 ], presumably due to better planning and preparation for SR production.…”
Section: Discussionsupporting
confidence: 88%
“…Despite the availability of reporting guidelines, the poor confidence ratings in this study suggest that SR authors do not adequately adhere to such guidelines. Our results also confirm the finding that SRs with review protocols have more strengths than SRs without review protocols [ 19 , 20 , 21 , 22 ], presumably due to better planning and preparation for SR production.…”
Section: Discussionsupporting
confidence: 88%
“…According to the AMSTAR-2 tool, the contents that required significant improvement were items 2 (study protocol and registration), 3 (explanation for the inclusion of study design), 7 (list of excluded studies with justifications), 8 (adequate details of included studies), 10 (funding sources of primary studies), and 12 (evaluation of the potential impact of risk of bias in primary studies on the synthesized results). The prospective registration of MAs’ protocol is an important process that can improve the transparency and reproducibility of the results ( Page et al, 2018 ), while a recent meta-epidemiological study ( Zheng et al, 2021 ) demonstrated that registered reviews of type 2 diabetes mellitus had a higher overall score of methodological quality. According to a previous study ( Page et al, 2018 ), there were 26,535 records on the most used registration website for systematic reviews, PROSPERO, up until 10th October 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the tool requiring an MA should have a prior protocol and register it on public websites (e.g., PROSPERO), as a preregistered protocol can inform the process of conducting an MA, reduce duplicate efforts, and help identify selective reporting bias (Page et al, 2014;Tawfik et al, 2020). An empirical study (Zheng et al, 2021) revealed that the prospective registration of protocols was positively associated with methodological and reporting quality of systematic reviews on type 2 diabetes mellitus. Selective inclusion of studies could result in biased or even entirely contrary findings (Palpacuer et al, 2019).…”
Section: Discussionmentioning
confidence: 99%